Spin current distribution in antiferromagnetic zigzag graphene nanoribbons under transverse electric fields - Jie Zhang (Nature Portfolio, 2021)
Abstract The spin current transmission properties of narrow zigzag graphene nanoribbons (zGNRs) have been the focus of much computational research, investigating the potential application of zGNRs in spintronic devices. Doping, fuctionalization, edge modification, and external electric fields have been studied as methods for spin current control, and the performance of zGNRs initialized in both ferromagnetic and antiferromagnetic spin states has been modeled. Recent work has shown that precise fabrication of narrow zGNRs is possible, and has addressed long debated questions on their magnetic order and stability. This work has revived interest in the application of antiferromagnetic zGNR configurations in spintronics. A general ab initio analysis of narrow antiferromagnetic zGNR performance under a combination of bias voltage and transverse electric field loading shows that their current transmission characteristics differ sharply from those of their ferromagnetic counterparts. At relatively modest field strengths, both majority and minority spin currents react strongly to the applied field. Analysis of band gaps and current transmission pathways explains the presence of negative differential resistance effects and the development of spatially periodic electron transport structures in these nanoribbons.